New constraints on the mid-IR EBL from the HESS discovery of VHE γ-rays from 1ES 0229+200 - van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2007)
Aims. To investigate the very high energy (VHE: > 100 GeV) y-ray emission from the high-frequency peaked BL Lac IES 0229+200. Methods. Observations of IES 0229+200 at energies above 580 GeV were performed with the High Energy Stereoscopic System (HESS) in 2005 and 2006. Results. IES 0229+200 is discovered by HESS to be an emitter of VHE photons. A signal is detected at the 6.6σ level in the HESS observations (41.8 h live time). The integral flux above 580 GeV is (9.4 ± 1.5 ± 1.9 ) × 10 cm s corresponding to ∼1.8% of the flux observed from the Crab Nebula. The data show no evidence for significant variability on any time scale. The observed spectrum is characterized by a hard power law (T = 2.50 ± 0.19 ± 0.10 ) from 500 GeV to ∼15 TeV. Conclusions. The high-energy range and hardness of the observed spectrum, coupled with the object's relatively large redshift (z = 0.1396), enable the strongest constraints so far on the density of the Extragalactic Background Light (EBL) in the mid-infrared band. Assuming that the emitted spectrum is not harder than T ≈ 1.5, the HESS data support an EBL spectrum σλ and density close to the lower limit from source counts measured by Spitzer, confirming the previous indications from the HEGRA data of IES 1426+428 (z = 0.129). Irrespective of the EBL models used, the intrinsic spectrum of IES 0229+200 is hard, thus locating the high-energy peak of its spectral energy distribution above a few TeV. © ESO 2007.
Keywords: BL lacertae objects: individual: IES 0229+200; Galaxies; Gamma rays: observations